Deposition of inhaled electronic cigarette aerosol in the human oral cavity. (February 2018) - Asgharian, Bahman; Price, Owen T.; Rostami, Ali A.; Pithawalla, Yezdi B.
Abstract: Increased use of electronic cigarette (EC) products has called for studying the health consequences from these new products. Government agencies such as the FDA are interested in toxicological, exposure data and other relevant information as a part of regulating the use of the products. A key step in risk assessment of EC products is to determine the inhaled dose of various constituents in the EC aerosol. Given the challenges in collecting human and animal data, mathematical models may guide and complement data collection. Models developed for combustible tobacco smoke may be improved and extended to EC aerosol to allow for higher volatility and hygroscopicity of the latter. Both these properties greatly affect the dynamics and deposition of inhaled aerosol. In this study, we developed a deposition model for EC aerosol based on realistic vaping scenarios. The model included several steps representing puff withdrawal into the oral cavity, mouth hold, dilution of the EC puff in the mouth with the subsequent dilution from inhaled air, inhalation of the puff into the lower respiratory tract, lung-hold, and exhalation. Results for deposition of individual constituents and droplet dynamics within the oral cavity of the respiratory tract will be presented in this publication. The model accounted for thermodynamic interactions between the droplet and vapor phases of each constituent in the aerosol mixture. Deposition from droplets and uptake of vapor constituents were calculated. The deposited mass fraction for each vapor constituent and droplets were also calculated based on the total mass of the inhaled constituents. The inhalation model developed in this study could help the academics, government agencies and tobacco manufacturers with development of risk models for EC use. Highlights: The temperature of inhaled aerosol mixture equilibrated rapidly with the body temperature in the oral cavity. Droplet diameter grew by approximately 50% at the end of mouth hold. The tissue dose depended on the saturation vapor pressure and their vapor-liquid partitioning at the mouth opening. Nicotine in the droplets and vapor phase contributed to the tissue absorption with droplet contribution being slightly higher.